Pregnancy Results in Lasting Changes in Knee Joint Laxity. Issue 2 (14th February 2019) - Chu, Stacey R.; Boyer, Elizabeth H.; Beynnon, Bruce; Segal, Neil A.
Abstract : Background: Altered joint laxity can contribute to joint dysfunction. Knee joint laxity has been shown to increase during pregnancy, but its long‐term persistence is unknown. Objective: To determine whether pregnancy leads to lasting increases in knee joint compliance and laxity that persist longer than 4 months postpartum. Design: Prospective cohort study. Setting: A motion analysis laboratory at an academic medical center. Participants: Fifty healthy women in their first trimester of pregnancy (mean ± SD 29.2 ± 4.3 years old and baseline body mass index 26.0 ± 5.4 kg/m 2 ) were recruited. Intervention: End‐range knee laxity and midrange joint compliance were measured during the first trimester and 19 ± 4 weeks postpartum. Anterior‐posterior and varus‐valgus laxity were measured using 3‐dimensional motion tracking while applying forces and moments in each respective plane using the Vermont Knee Laxity Device. Nonlinear models were constructed to assess relations between applied forces and joint translation, comparing early pregnancy with postpartum. Outcomes: Multiplanar knee laxity and compliance. Results: Peak varus‐valgus (20‐22%; P = .001) and posterior translation (51%; P < .001) of the tibia relative to the femur decreased from baseline, with a concomitant decrease in laxity ( P < .001) and compliance ( P = .039) in the coronal plane and in the posterior direction in primiparous ( P = .009) and multiparous ( P = .014) women. For primiparous women, laxity ( P < .001) and compliance ( P = .009) increased in the anterior direction. Conclusions: Pregnancy resulted in a lasting decrease in multiplanar knee laxity and compliance in the varus and posterior directions with an increase in anterior compliance. The effects of these changes in laxity and compliance of the passive stabilizers on knee loading patterns, articular contact stresses, and risk for osteoarthritis and other musculoskeletal disorders will require additional research. Level of Evidence: II